2021
DOI: 10.3390/molecules26061799
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide Hydratase Modification Using Computational Design and Docking Analysis for Improved Binding Affinity in Cyanide Detoxification

Abstract: Cyanide is a hazardous and detrimental chemical that causes the inactivation of the respiration system through the inactivation of cytochrome c oxidase. Because of the limitation in the number of cyanide-degrading enzymes, there is a great demand to design and introduce new enzymes with better functionality. This study developed an integrated method of protein-homology-modelling and ligand-docking protein-design approaches that reconstructs a better active site from cyanide hydratase (CHT) structure. Designing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Cyanide hydratase has been shown to be the key enzyme in the cyanide degradation pathway in previous studies [ 23 ]. This study confirmed the importance of cyanide hydratase in pathway determination using KEGG orthology; K10675 in the Trichoderma genus.…”
Section: Resultsmentioning
confidence: 99%
“…Cyanide hydratase has been shown to be the key enzyme in the cyanide degradation pathway in previous studies [ 23 ]. This study confirmed the importance of cyanide hydratase in pathway determination using KEGG orthology; K10675 in the Trichoderma genus.…”
Section: Resultsmentioning
confidence: 99%
“…The activities of the whole E. coli cells (153-600 U/mg dry weight) and CFE (736 U/mg protein) [33] were substantially higher in comparison with the endogenous enzymes, whereas the activities of the purified enzymes from the homologous and heterologous producers were similar (100-1324 U/mg protein; Table S1) [29,31,33]. Further enhancement of CynH action on fCN may be possible by the specific mutations recently proposed in silico [34].…”
Section: Introductionmentioning
confidence: 91%